Kajian Kinerja Simpang Tak Bersinyal di Kawasan Universitas Iskandar Muda Berdasarkan Karakteristik Arus Lalu Lintas - Febrina Dian Kurniasari; Alfisyahrin Alfisyahrin; Marini Bravikawati; Tjut Rizqi Maysyarah Hadi; Michel Kasaf (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Unsignalized intersections often become critical points of traffic problems due to increasing traffic volume that is not balanced with intersection capacity, resulting in delays, queues, and potential conflicts, especially during peak hours. This condition also occurs at the Unida Intersection (Universitas Iskandarmuda) in Banda Aceh, which serves traffic movements from campus areas, residential zones, and surrounding commercial activities. This study aims to analyze traffic flow characteristics and intersection performance using the Indonesian Highway Capacity Guidelines (PKJI 2023). The data used include traffic volume and geometric conditions of the intersection, which are then analyzed based on parameters such as capacity, degree of saturation, delay, queue probability, and level of service. The results show that the highest traffic volume occurs during the afternoon peak hour, reaching 1,089 pcu/hour, with a degree of saturation of 0.65. The average intersection delay is 12.989 seconds per vehicle, with a queue probability ranging from 17.47% to 36.09%. The level of service is classified as C, indicating that traffic flow remains stable but begins to be affected by congestion. Overall, the intersection still operates adequately however, further evaluation is needed to anticipate future increases in traffic volume.